2022
DOI: 10.3389/fnut.2022.891339
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoids for Metabolic Syndrome: Meta-Analysis Evidences Toward Personalized Prevention and Treatment Management

Abstract: The metabolic syndrome (MS) is a multifactorial syndrome associated with a significant economic burden and healthcare costs. MS management often requires multiple treatments (polydrug) to ameliorate conditions such as diabetes mellitus, insulin resistance, obesity, cardiovascular diseases, hypertension, and non-alcoholic fatty liver disease (NAFLD). However, various therapeutics and possible drug-drug interactions may also increase the risk of MS by altering lipid and glucose metabolism and promoting weight ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 189 publications
0
2
0
Order By: Relevance
“…In human neuroblastoma cells, curcumin was found to increase mitochondrial fusion activity, decrease fission machinery, and enhance biogenesis [ 165 ]. The results of clinical studies have been reviewed recently, and suggest that curcumin may be beneficial in patients with metabolic diseases [ 166 , 167 ].…”
Section: Target Mitochondrial Fission For Antioxidants In Metabolic D...mentioning
confidence: 99%
“…In human neuroblastoma cells, curcumin was found to increase mitochondrial fusion activity, decrease fission machinery, and enhance biogenesis [ 165 ]. The results of clinical studies have been reviewed recently, and suggest that curcumin may be beneficial in patients with metabolic diseases [ 166 , 167 ].…”
Section: Target Mitochondrial Fission For Antioxidants In Metabolic D...mentioning
confidence: 99%
“…Together with curcumin, which is the most abundant polyphenol (~77%), the rhizome of Curcuma longa also contains other phenol-based compounds called curcuminoids, the most important being desmethoxycurcumin (~15%) and bisdemethoxycurcumin (~3%) [3,4]. Considering that curcumin prevails over the other congeners, most of the preclinical literature in this field has explored the effects of the pure compound in several experimental systems, whereas only a few papers have studied the biological properties of curcuminoids [5][6][7][8][9]. Unlike preclinical research, which suggested a beneficial role for curcumin in neurodegenerative, cardiovascular, hematological, and infectious diseases, only a few studies have been carried out to confirm these therapeutic effects in humans [10][11][12].…”
Section: Introductionmentioning
confidence: 99%